AKIBAT HUKUM ATAS WANPRESTASI YANG TERJADI PADA PRAKTIK ENDORSEMENT DALAM PERSPEKTIF KUHPERDATA (Faculty of Law, University of Palembang, 2023)
The endorsement agreement is based on an agreement between the endorser and the online shop. The provisions of each party contained in the work contract must be implemented by the parties, both their rights and obligations. The occurrence of negligence/default on a mutual agreement will give rise to legal consequences for the parties. Default is regulated in article 1238 of the Civil Code. The debtor is declared negligent by means of a warrant, or by means of a similar deed, or based on his own strength and commitment, namely if this agreement means that the debtor must be deemed negligent after the specified time has elapsed. Default is a breach of contract which means that one party does not carry out its performance in accordance with the agreed agreement. Default of course has juridical consequences where the party committing the default must bear the legal consequences of the default. This compensation is clearly stated in article 1246 of the Civil Code where the compensation referred to here is in the form of costs that have actually been incurred, loss which means loss due to damage to the creditor's property caused by the debtor and also in the form of interest, namely the profit that should have been obtained.